ISCHEMIA AS A SENSITIZER TO THE EFFECTS OF DIGITALIS - POZO, EFREN C DEL (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
In the cat the posterior leg muscle rendered ischemic by occlusion of the abdominal aorta or the femoral artery provides a medium in which muscular contractions caused by indirect stimulation are markedly diminished With reestab-lishment of normal circul
BOL INST ESTUD MED BIOL
Keywords: ISCHEMIA, SENSITIZER, EFFECTS, DIGITALIS; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA